2018
DOI: 10.3390/rs10081249
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Hyperspectral Sensing of Paddy Fields at the Booting Stage and PLS Regression can Assess Grain Yield

Abstract: Canopy hyperspectral (HS) sensing is a promising tool for estimating rice (Oryza sativa L.) yield. However, the timing of HS measurements is crucial for assessing grain yield prior to harvest because rice growth stages strongly influence the sensitivity to different wavelengths and the evaluation performance. To clarify the optimum growth stage for HS sensing-based yield assessments, the grain yield of paddy fields during the reproductive phase to the ripening phase was evaluated from field HS data in conjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 74 publications
3
31
0
Order By: Relevance
“…As such, only two images were required for estimating BT and NU a few days before each of the two TdFs. Yield prediction accuracy was higher at the booting stage (R 2 from 0.61 at tillering to 0.77 at booting with two images), which is consistent with a recent study [39] that showed that the best timing for predicting yield from hyperspectral measurements was indeed the booting stage. The alternative approach of using an intermediate image approximately seven to ten days after the first TdF is useful only in certain cases and, especially, if one is required to predict the plant's N content (NU or NC) at the maturity stage.…”
Section: Discussionsupporting
confidence: 90%
“…As such, only two images were required for estimating BT and NU a few days before each of the two TdFs. Yield prediction accuracy was higher at the booting stage (R 2 from 0.61 at tillering to 0.77 at booting with two images), which is consistent with a recent study [39] that showed that the best timing for predicting yield from hyperspectral measurements was indeed the booting stage. The alternative approach of using an intermediate image approximately seven to ten days after the first TdF is useful only in certain cases and, especially, if one is required to predict the plant's N content (NU or NC) at the maturity stage.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with other imaging modalities, such as natural color and multispectral imagey, hyperspectral imagery consists of hundreds of spectral bands, arranged in a narrower bandwidth, and is thus capable of providing more detailed spectral information which is of great importance for estimating complex plant traits, such as yield [ 15 ]. For example, the grain yield of paddy fields was predicted in the northern part of Vientiane in Laos, and the booting stage was found to be the best prediction time using hyperspectral data [ 16 ]. Also, wheat yield was successfully estimated using 190 hyperspectral narrow bands acquired from a UAV platform before harvest in Minnesota [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In gramineous crops, such as rice and wheat, the influence of soil background is prominent during early growth stages, and it decreases as vegetation cover (VC) increases. Numerous studies have shown that the appearance of panicles can not only change the light distribution in a crop canopy, but also considerably affect canopy spectral reflectance [25][26][27][28]. Inoue et al [29] and Asilo et al [30] also reported that panicles influence the relationship between X-band and LAI in rice.…”
Section: Introductionmentioning
confidence: 99%